Structural characterization of the c-terminal domain of endolysin plymw2 and interaction with the peptidoglycan of Staphylococcus aureus - Leite, Marlene Pimentel (2022)
Staphylococcus aureus (S. aureus) is a major pathogen with the ability to acquire resistance to most antibiotics and a threat for global health. S. aureus is remarkably capable of developing resistance to commonly used antibiotics and novel approaches to treat these infections are urgent. The phage lytic enzymes or endolysins are alternatives with high potential for antibacterial therapy. PlyMW2 lysin found in a prophage in S. aureus subspecies MW2 has two structural/functional domains: a CHAP domain and a divergent cell wall-binding domain (CBD) with no known structural homologs. The main goal is to determine how this unique CBD interacts with the S. aureus cell wall, specifically with its peptidoglycan. The gene for CBDMW2 was amplified from genomic DNA and cloned in modified pET vectors. The overexpressed proteins were purified and used for the structural and interactions studies. Peptidoglycan was extracted, purified from staphylococcal cultures and digested with muralytic enzymes. The resulting muropeptides were purified by reverse phase-HPLC and analyzed and characterized by NMR and ESI-MS. The interaction of CBDMW2 with S. aureus cells was analyzed using Fluorescence microscopy and showed that the GFP-CBDMW2 binds to localized regions of the cell wall, likely where the peptidoglycan is more accessible. MicroScale Thermophoresis was used to measure the interaction between the CBDMW2 and a mixture of muropeptide digested with mutanolysin and amidase, yielding fragments containing peptides with different lengths. An apparent KD of 211±110 nM was obtained showing that CBDMW2 binds to the peptide component with high affinity. Backbone resonance assignments were achieved from NMR 3D-experiments and used to analyze the 1H-15N-HSQC titration of the CBDMW2 with a monomeric muropeptide. CBDMW2 NMR structure revealed SH3b-type fold although low/none sequence homology, with striking differences on the loop regions. The binding region identified for the monomeric muropeptide reveals unique features involving non-conserved amino acids with structural and functional homologs.